COVID-19’s Impact on the Student Learning Process in Rwandan Higher Education Institutions - Twesige, Daniel; Gasheja, Faustin; Isae Misago, Kadhafi; Muvunyi, Eugen (International Journal of African Higher Education, 2021)
The coronavirus pandemic has not only challenged health systems, but has also had a significant impact on education systems across the globe. This study analysed COVID-19’s impact on the student learning process in Higher Education Institutions in Rwanda. A quantitative research design was adopted and pragmatism was selected as the research philosophy. Primary data was collected from 1 170 students in 30 institutions using a closed-ended questionnaire. The data was analysed using descriptive and inferential statistical tools. The results indicate that the pandemic has led to changes in the academic calendar, suspension of examinations, and final year students being unable to conduct research and serve internships. It has also affected the quality of learning and learning from peers due to social distancing. Students in rural areas and those from vulnerable families have been worst affected. Key words: COVID-19, learning, higher education institutions, online learning, students